Investigation of Adhesion and Tribological Behavior of Borided AISI 310 Stainless Steel - Gunes,Ibrahim (2016)
In the present study, the effects of the boriding process on adhesion and tribological properties of AISI 310 steel were investigated. Boriding was performed in a solid medium consisting of Ekabor-II powders at 1123 and 1323K for 2 and 6 h. The boride layer was characterized by optical microscopy, the X-ray diffraction technique and the micro-Vickers hardness tester. The X-ray diffraction analysis of the boride layers on the surface of the steels revealed the existence of FexBy, CrxBy and NixBy compounds. Depending on the chemical composition of substrates, the boride layer thickness on the surface of the AISI 310 steel was found to be 56.74 μm. The hardness of the boride compounds formed on the surface of the AISI 310 steel ranged from 1658 to 2284 HV0,1, whereas the Vickers hardness value of the untreated steel AISI 310 was 276 HV0,1. The wear tests were carried out in a ball-disc arrangement under a dry friction condition at room temperature with an applied load of 10N and with a sliding speed of 0.3 m/s, at a sliding distance of 1000m. The wear surfaces of the steel were analyzed using an SEM microscopy and X-ray energy dispersive spectroscopy EDS. It was observed that the wear rate of unborided and borided AISI 310 steel ranged from 4.57 to 71.42 mm3/Nm.